Network pharmacology and experimental verification-based strategy to explore the underlying mechanism of Liu Jun An Wei formula in the treatment of gastrointestinal reactions caused by chemotherapy for colorectal cancer - Li, Gaobiao; Liu, Liying; Yin, Yiran; Wang, Mengmeng; Wang, Lei; Dou, Jianwei; Wu, Hongwei; Yang, Yufei; He, Bin (Frontiers in Pharmacology, 2022)
Background: Derived from “Liu Jun Zi Decoction”, a classical prescription of Tradition Chinese Medicine, Liu Jun An Wei formula (LJAW) has been used for the prevention and control of gastrointestinal reactions caused by chemotherapy for colorectal cancer (CRC) for many years. Its molecular mechanism remains to be further explored. Objective: To clarify the mechanism of LJAW in preventing and controlling gastrointestinal reactions caused by chemotherapy for CRC systematically. Methods:The 5-FU intervention model was established to observe the effect of LJAW on mice and organoids injured by 5-FU. The ingredients of LJAW were analyzed and identified by UPLC-Q-TOF-MS technology. Targets of LJAW and chemotherapy-induced gastrointestinal reactions were collected from several databases. “Ingredient-target” network and protein-protein interaction network were constructed based on network pharmacology. Then, gene ontology (GO) functional analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed. Subsequently, molecular docking method was used to verify the interaction between the core ingredients and key targets. The results were validated by both in vivo experiments and organoid experiments. Western Blot (WB) was used to analyze the influence of LJAW on PI3K, AKT1, MAPK1, MAPK14 proteins as key targets and their phosphorylated proteins, and RT-qPCR and WB were used to detect mRNA and protein expression of apoptosis-related gene PUMA. Results: Compared with the 5-FU group, the LJAW group had better morphology in mouse small intestine and organoids. In total, 18 core ingredients and 19 key targets were obtained from 97 ingredients and 169 common targets. KEGG analysis showed that these common targets were involved in PI3K/Akt, MAPK, apoptosis and other signal pathways, which are closely related to gastrointestinal injury. Both experiments have confirmed that LJAW may effectively lower the expression of phosphorylated proteins of key targets PI3K, AKT1, MAPK1, and MAPK14 and may also reduce the mRNA and protein expressions of PUMA. Conclusion: LJAW has apparent protective effect on small intestine and intestinal organoids injury induced by 5-FU. The results reveal that LJAW regulates apoptosis-related genes through PI3K/AKT and MAPK signaling pathways, alleviating the intestinal mucosa injury, preventing and controlling gastrointestinal reactions caused by chemotherapy for CRC.